THE NEOPROTEROZOIC AND PALAEOZOIC PALAEOMAGNETIC DATA FOR THE SIBERIAN PLATFORM: FROM RODINIA TO PANGEA - Smethurst M.A.; Torsvik T.H.; Khramov A.N. (My University, 1998)
Using the most reliable palaeomagnetic data from the Siberian Platform we have constructed an apparent polar wander (APW) path extending between 1100 Ma and 250 Ma. From this we derive the palaeo-latitudinal drift history and orientation change of Siberia through the Neoproterozoic and Palaeozoic. Comparison of selected palaeomagnetic data from Siberia north and south of the Viljuy basin confirms a mid-Palaeozoic anticlockwise rotation of northern Siberia relative to southern Siberia. The rotation of approximately 20 degrees was first proposed by Gurevich in 1984. The Viljuy basin runs approximately east west along latitude 64°N. APW paths based on data compilations including, for example, Ordovician data from both the Lena river section (south) and Moyero river section (north) will be adversely affected by this relative rotation. The palaeomagnetic data indicate an inverted orientation for Siberia in `Rodinia times' (ca. 750 Ma) in a palaeo-latitudinal belt between 15°S and 20°N. This is inconsistent with a palaeo-position on the northern margin of Rodinia if the rest of Rodinia is located according to palaeomagnetic data from Laurentia, Baltica and East Gondwana. The final convergence between Siberia and Baltica is poorly constrained by palaeomagnetic data. At 360 Ma Siberia was in an inverted position in mid-northerly latitudes, separated from Baltica (to the south) by an east west oceanic tract approximately 1500 km wide. The next palaeomagnetic constraint on the position of Siberia is at 250 Ma which puts Siberia and Baltica together at the northern end of Pangea. The convergence of the two is characterised by the northerly drift of Baltica and clockwise rotation of Siberia. Although the APW paths for Siberia, Baltica and Laurentia differ, they imply broadly similar palaeo-latitudinal drift trends for the three continents. During the time-period studied all three continents start in southerly/equatorial palaeo-latitudes, drift south, then drift north, changing drift sense at approximately the same time. The smaller scale differences in palaeo-latitude change reflect the opening and closing of intervening oceans. The overall pattern of movements may reflect a large scale (temporal and spatial) geodynamic system which survived the construction and destruction of supercontinents. If we hold to the concept that true polar wander is not significant, we conclude that large continents, although intermittently separated by oceanic tracts, may be driven across the globe in a weak union for periods of 800 Ma or more.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская